Hans Jonas's input into the philosophy of responsibility - Dzwonkowska, Dominika (Studia Ecologiae et Bioethicae, 2007)
Article presents the concept of responsibility in Hans Jonas’s philosophy. Biocentric character of his ethics gives it new outlook to the phenomenon of responsibility. It seems that mankind cannot anymore afford ignoring environmental problems. And Jonas’s imperative of responsibility is the answer to the ecological crisis. It is based on Kant’s imperative, but new imperative goes beyond anthropocentric ethics to biocentric ethics. It aimed at preserving all forms of life, life in its rich diversity. Its basic motivation is fear of progressing destruction of nature, this fear, when dosed properly by politicians, leads to undertaking actions aiming at preserving nature from man’s activity. It seems that taking responsibility for nature may be way to preserve it.